2017
DOI: 10.3892/ijmm.2017.3037
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling pathway promotes osteogenic differentiation of mesenchymal stem cells by enhancing BMP9/Smad signaling

Abstract: Notch is an important pathway in that it regulates cell-to-cell signal transduction, which plays an essential role in skeletal remodeling. Bone morphogenetic protein (BMP)9 has been regarded as one of the most efficient BMPs by which to induce osteogenic differentiation in mesenchymal stem cells (MSCs). Understanding the interaction between Notch and BMP9 signaling is a critical issue for optimizing the application of MSCs and BMPs in bone tissue engineering. In the present study, we investigated the role of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 56 publications
1
71
1
1
Order By: Relevance
“…Collected tissue samples were fixed in 10% buffered formalin overnight and embedded in paraffin. Serial sections were stained with hematoxylin and eosin (H&E, Sigma-Aldrich), Masson’s trichrome (Sigma-Aldrich), and alcian blue (Sigma-Aldrich) [17,27,38,53].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collected tissue samples were fixed in 10% buffered formalin overnight and embedded in paraffin. Serial sections were stained with hematoxylin and eosin (H&E, Sigma-Aldrich), Masson’s trichrome (Sigma-Aldrich), and alcian blue (Sigma-Aldrich) [17,27,38,53].…”
Section: Methodsmentioning
confidence: 99%
“…BMP9, also known as growth differentiation factor 2 (GDF-2)[25], was originally isolated from the fetal mouse liver [25,26]. Bone formation involves BMP9 acting through the Notch signaling pathway [14,24,27]. Several metabolic processes are regulated by BMP9, including glucose and lipid metabolism [28,29], iron metabolism [30], endothelial function, and angiogenesis [31,32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMMSCs are non-hematopoietic multipotent stem cells which can differentiate into adipogenic, osteogenic, and chondrogenic lineages (16, 17). These cells can secrete and respond to different signaling molecules and undergo osteogenic differentiation thereby playing an essential role in bone homeostasis (18, 25). Previous studies have shown that virus infection can affect functions of BMMSCs (21, 22, 26), but it is unclear whether BMMSCs are susceptible to alphavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although many signals, such as Notch, Wnt/β‐catenin, and MAPKs, take part in osteogenic differentiation in MSCs. BMP/Smad signal is identified as the canonical pathway for BMPs …”
Section: Discussionmentioning
confidence: 99%